Revitalisasi Kawasan Terasering melalui Pendekatan Urban-Rural Exchange Design di Oyama Senmaida, Kamogawa, Jepang - Pandu Purwandaru; Aoki Hironobu (Jurnal Ilmu Sosial dan Humaniora, 2024)
Since 1960, the area of rice terraces in Japan has begun to decrease drastically due to a lack of human resources. Oyama Senmaida is a rice terrace area that successfully managed a revitalization program through an urban-rural exchange approach and was included among Japan's 100 top rice terraces. Based on the achievements of this organization, this research was carried out to understand development patterns from the design development aspect to the evaluation of programs through direct interviews with staff at Oyama Senmaida and surveys from the activities held. From the results of this research, it can be concluded that the revitalization design strategies carried out by Oyama Senmaida include raising the foundation of design ideas through local and external potential and dividing activity programs into preservation and new program development. Regarding program details, there are three categories of activities, namely ownership and trust, workshops and experience, and other programs. In the context of evaluation, supporting elements in producing a sustainable revitalization program, including building internal and external cooperation networks; planning income and funds from the government or private sector for development; and targeting market participants in the surrounding area and building aspects of publication through newspapers and online media.